Nigerian Pentecostal Mission in Europe: Ecumenical and Secular Relations in Britain - Adenekan-Koevoets, Bisi (Ecclesial Futures, 2023)
African churches face diverse obstacles while attempting cross-cultural mission in the West. These include the influence of external forces such as racism, lack of understanding of European cultures, lack of worship spaces and various perceptions that many wider indigenous Europeans have about Africans and their churches, particularly their theological beliefs. These external factors impose real challenges, which are beyond the control of the leaders of diaspora African churches and interfere with the effort to build relations with the wider white indigenous European host population, whether spiritual or secular. This qualitative study explores the different ways through which Nigerian-initiated churches in London are engaging with British society, both ecumenically and as a social force within the communities. There are indications that a few of the larger churches are building ecumenical relations with mainline Britishchurches, although this is prevalent at leadership level. Similarly, they are well-enough resourced to embark on social community projects which are beneficial to nationals of all races and political activities to court the British royal and political elite and aretherefore establishing their presence within and creating pathways to British society.